2014
DOI: 10.1186/1471-2261-14-47
|View full text |Cite
|
Sign up to set email alerts
|

Possible extracardiac predictors of aortic dissection in Marfan syndrome

Abstract: BackgroundAccording to previous studies, aortic diameter alone seems to be insufficient to predict the event of aortic dissection in Marfan syndrome (MFS). Determining the optimal schedule for preventive aortic root replacement (ARR) aortic growth rate is of importance, as well as family history, however, none of them appear to be decisive. Thus, the aim of this study was to search for potential predictors of aortic dissection in MFS.MethodsA Marfan Biobank consisting of 79 MFS patients was established. Thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 26 publications
1
18
1
2
Order By: Relevance
“…A clear tendency of increased DM and ICM/SOAM of the right and left renal artery in patients who underwent aortic surgery (Group B, Group C) compared to patient who did not have surgery (Group A) indicates the possible predictive role of these tortuosity metrics in differentiating between the more benign and the more malignant form of MFS as proposed in our previous study for the classification of aortic involvement in this syndrome [31].…”
Section: Sum Of Angles Metric (Soam) Is Assessed By Subdividing the Asupporting
confidence: 52%
See 1 more Smart Citation
“…A clear tendency of increased DM and ICM/SOAM of the right and left renal artery in patients who underwent aortic surgery (Group B, Group C) compared to patient who did not have surgery (Group A) indicates the possible predictive role of these tortuosity metrics in differentiating between the more benign and the more malignant form of MFS as proposed in our previous study for the classification of aortic involvement in this syndrome [31].…”
Section: Sum Of Angles Metric (Soam) Is Assessed By Subdividing the Asupporting
confidence: 52%
“…In our previous studies we demonstrated that increased serum TGF-β levels, the upregulation of MMP-3 in the peripheral blood mononuclear cells, the presence of striae atrophicae (stretch marks), alterations in the homocysteine metabolism and polymorphisms of the enzymes involved in this latter process could be related to more serious forms of aortic involvement in MFS [16,31]. However, further investigation is necessary to elucidate whether the above findings together with the various tortuosity metrics could eventually enable us to develop a multivariate model and a score system to predict the severity of the aortic outcome.…”
Section: Sum Of Angles Metric (Soam) Is Assessed By Subdividing the Amentioning
confidence: 99%
“…TGF-β1 concentration in serum accounts for both, the amount of cytokine in the systemic circulation and the amount released from platelet α-granules during clotting process [ 13 ]. TGF-β1 concentration detected in serum should be referred critically due to the strong positive correlation between platelet count and the serum concentration of TGF-β1 [ 14 ]. TGF-β1 variation among studies ( Table 4 ) illustrates the importance of the blood sample used for testing and should always be taken into account when comparing results from different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using both human blood plasma and serum indicate increased TGF-β1 values in Marfan patients with DPAA [ 3 , 5 , 14 , 15 ]. We show that non-marfanoid patients with DPAA also have elevated plasma levels of TGF-β1 compared to the reference group.…”
Section: Discussionmentioning
confidence: 99%
“…Так, например, в исследовании Ágg B, et al (2014) показано 3 наиболее значимых параметра, помогающих предсказать риск диссекции аорты у пациентов с СМ, а именно, наличие атрофических стрий, уровень TGF-β и матриксных металлопротеиназ-3 в сыворотке крови. Согласно этому исследованию, пациентов с СМ и РКА следует классифицировать на злокачественный и доброкачественный типы, что должно влиять на выбор сроков профилактического протезирования аорты [130].…”
Section: возможности леченияunclassified